From erosion to fluency: reversing language shift in Chinese Australian households - Wang, Yining; Zhang, Jie (Frontiers in Psychology, 2025)
Since the late 20th century, China-born population has emerged as the third largest source of permanent immigrants to Australia. This study aims to explore the dynamics of heritage bilingualism of twenty-five 1.5-generation Chinese-Australian adolescents and young adults, a cohort that is often overlooked in migration studies. Through family questionnaires, semi-structured interviews, field observations, and linguistic samples, the study explores how the age at migration influences language attitudes, proficiency performance, cultural identity, and socialization patterns among three age-of-migration cohorts. While the study confirms a common trend of language erosion across all age cohorts, it distinctively delineates the varying degrees of language attrition specifically associated with the age at migration. Meanwhile, the research spotlights exceptional cases of maintained heritage language fluency, underscoring how family strategies, child agency, educational policies, and literary engagement are crucial in combating language erosion and fostering heritage language proficiency. The finding underscores the importance of understanding the unique linguistic journeys across age-of-migration groups to better support their language development and maintenance. It provides valuable insights for families, educators, and policymakers working to sustain minority languages within a dominant English-speaking environment.